MENINGKATKAN PEMAHAMAN KONSEP PERKALIAN BILANGAN CACAH MELALUI PERMAINAN EDUKATIF ULAR TANGGA MATA PELAJARAN MATEMATIKA PADA SISWA KELAS III - Qiztia Zalwa A. Moito; Fatimah Djafar; Febry Rizki Susanti Kalaka (Al-mujahidah, 2026)
Research This research aims to describe the application of educational games of snakes and ladders in improving the understanding of the concept of multiplication of whole numbers in mathematics subjects for third-grade students at the Muhammadiyah Pone Private Islamic Elementary School in West Limboto. This type of research is a classroom action research of third-grade students totaling 26 people. The object of this research is the application of educational games of snakes and ladders to third-grade students at MIS Muhammadiyah Pone. The data analysis techniques used in this research are analysis of test results and analysis of observation results. Based on the results of Classroom Action Research that has been carried out on third-grade students at MIS Muh. Pone, it can be concluded that the use of educational games of snakes and ladders can improve students' understanding of the concept of multiplication of whole numbers in mathematics subjects. This improvement can be seen from the students' understanding that has changed after the application of educational games of snakes and ladders in the learning process. In the initial condition before the action was carried out, there were 17 students out of 26 students who had not achieved learning mastery with a percentage of 65.38%, while students who had achieved mastery were only 9 students or 34.62%. After carrying out learning activities using the educational game media snakes and ladders, the number of students who completed the game increased to 24 students or 92.31%, while students who had not completed it decreased to 2 students or 7.69%.